Chasing Polycyclic Natural Products: 5/6/5‐ or 5/6/6‐Carbotricyclic Scaffold Construction via Stereodivergent Diels‐Alder Reaction of Chiral Hydrindanes and Their Boron Complexes. Issue 26 (22nd February 2022) - Stöckl, Yannick; Fellmeth, Thomas; Bauer, Florian; Wank, Bianca; Frey, Wolfgang; Claasen, Birgit; Zens, Anna; Köhn, Andreas; Laschat, Sabine
Abstract: Chiral trans ‐hydrindanes (bicyclo[4.3.0]nonanes) are important building blocks of polycyclic natural products. In order to access 5/6/5‐ and 5/6/6‐carbotricyclic scaffolds scope and limitation of [4+2] cycloadditions of tetrahydroindanones with various dienes were studied. Cyclopentadiene gave a tetracylic endo ‐( R, R )‐diastereomer under acid‐catalysis, whereas thermal conditions provided the endo ‐( S, S )‐diastereomer with the opposite diastereofacial selectivity. The stereodivergent outcome was rationalized by high‐level quantum‐chemical computations which revealed the acid‐catalysis to be a kinetically controlled reaction and the thermal cycloaddition to be under thermodynamic control. Stereochemical assignment of the cycloadducts was facilitated by conversion of the 1, 3‐dicarbonyls with BF3  ⋅ OEt2 into BF2 ‐chelate complexes. Subsequent thermal Diels‐Alder reaction of BF2 ‐ or BBN‐chelates (from 9‐BBN‐OTf) gave endo / exo ‐mixtures of the ( R, R )‐ and ( S, S )‐diastereomers, while more elevated temperatures yielded primarily the endo / exo ‐( S, S )‐diastereomers. Thermal [4+2] cycloadditions with 2, 3‐dimethylbutadiene proceeded with lower diastereoselectivity as the reaction was kinetically controlled according to calculations. Attempted Diels‐Alder‐reactions with furan gave furyl‐substituted indanones rather than cycloadducts. Abstract : The Diels‐Alder reaction of 4‐substituted tetrahydroindanones with cyclic and acyclic dienes was examined. By choosing acidic or thermal conditions, the diastereoselectivity on the newly formed ring could be controlled and was rationalized by high‐level computations. Additionally, boron complexation of the 1, 3‐dicarbonyl moiety exhibited unexpected selectivity in the cycloaddition.